Incidence and Neurological Sequelae of Trigeminal Nerve Injury Following Mandibular Fracture Repair: A Prospective Study - Hassan Masood, Malik Talha Saad, Ayesha Bibi, Atif Iqbal Butt, Syed Arslan Haider, Usman Mahmood (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Trigeminal nerve injury is a recognized complication of mandibular fracture repair, particularly due to the close anatomical proximity of the inferior alveolar and mental nerves to surgical sites. This study aimed to evaluate the incidence, type, and recovery outcomes of trigeminal nerve injury following open reduction and internal fixation (ORIF) for mandibular fractures. Methods: A prospective study was conducted from January 2022 to March 2023 at Punjab Dental Hospital, Lahore, and Federal Government Polyclinic Hospital, Islamabad. A total of 100 patients undergoing ORIF for mandibular fractures were enrolled. Neurosensory assessments for mental and inferior alveolar nerves were performed preoperatively and postoperatively using standardized clinical tests. Patients were followed for 6 months at defined intervals and outcomes were graded using the modified Medical Research Council (MRC) Scale. Results: Of the 100 patients (mean age 33.8 ± 8.6 years; 72% male), 33 (33%) developed trigeminal nerve dysfunction postoperatively. Mental nerve involvement was more common (21%) than inferior alveolar nerve injury (12%). Most injuries were associated with parasymphysis and body fractures. At the 6-month follow-up, 18 patients (54.5%) had complete recovery, 9 (27.3%) showed partial recovery, and 6 (18.2%) had persistent sensory deficits. Conclusion: Trigeminal nerve injury is a relatively common postoperative complication in mandibular fracture repair, with the mental nerve most frequently affected. Although the majority of cases resolve over time, a significant proportion may result in long-term dysfunction. Careful surgical planning and routine neurosensory monitoring are essential for optimizing patient outcomes. Keywords: Mandibular fracture, Trigeminal nerve injury, Mental nerve, Inferior alveolar nerve, Neurosensory deficit, ORIF